Adolphe Duperly's rebellion prints and the historical moment of emancipation. Issue 1 (2nd January 2022) - Bohls, Elizabeth A.
ABSTRACT: French lithographer Adolphe Duperly created three remarkable prints in 1833, between Jamaica's last slave revolt (1831–1832) and Emancipation (1834). He appropriated images from James Hakewill's Picturesque Tour of [ … ] Jamaica, calling his prints "occurrences, " a designation whose historical specificity contrasts with the timelessness of the picturesque. Duperly adds rebelling slaves, depicting them in ambiguous ways evoking both threat and celebration. Their figures are individualized, unlike earlier depictions of the enslaved as staffage figures or disciplined laborers. Colored by white paranoia, Duperly's images nonetheless suggest an incipient coming to terms with a changed relationship between free and formerly enslaved Jamaicans. His 1838 lithograph, Commemorative of the Extinction of Slavery, continues this trend. Unlike contemporaries Hakewill and Joseph Kidd, Duperly settled in Jamaica, establishing a business maintained by his family into the twentieth century. His commitment to the colony helps explain the unprecedented visibility given to black Jamaicans in his art.